2010
DOI: 10.1097/pai.0b013e3181b6a741
|View full text |Cite
|
Sign up to set email alerts
|

A High Number of CD8+ T Cells Infiltrated in NSCLC Tissues is Associated With a Favorable Prognosis

Abstract: We investigated the number of intratumoral tumor-infiltrating lymphocytes (TILs), including CD4(+), CD8(+), and CD25(+) T cells, in nonsmall cell lung cancers (NSCLC) and their correlation with patient survival time. Tumor specimens from 30 NSCLC patients were consecutively obtained during surgery. Patient survival status was monitored. Based on survival time, patients were divided into 2 groups: 5-year survival group and 5-year nonsurvival group. CD4(+), CD8(+), and CD25(+) T cells that infiltrated tumors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 17 publications
4
39
0
1
Order By: Relevance
“…Retrospective analysis has suggested that high tumor infiltration with CD4+ and/or CD8+ T cells is associated with improved survival of patients with early-stage (stages I to IIIA) NSCLC [23][24][25]. In another study, the presence of higher numbers of tumor-infiltrating CD8+ T cells in cancer nests compared with cancer stroma in patients with stage IV NSCLC was an independent predictor of better survival; similar results were found for infiltrating macrophages [26].…”
Section: Rationale For Immunotherapy In Nsclcsupporting
confidence: 64%
“…Retrospective analysis has suggested that high tumor infiltration with CD4+ and/or CD8+ T cells is associated with improved survival of patients with early-stage (stages I to IIIA) NSCLC [23][24][25]. In another study, the presence of higher numbers of tumor-infiltrating CD8+ T cells in cancer nests compared with cancer stroma in patients with stage IV NSCLC was an independent predictor of better survival; similar results were found for infiltrating macrophages [26].…”
Section: Rationale For Immunotherapy In Nsclcsupporting
confidence: 64%
“…This is important, because different localization of the lymphocytes may indicate a different prognostic impact. 9,20,21 Furthermore, VEGF-A/VEGFR-2 expression was scored in neoplastic epithelial cells; however, we know that this is only a piece of the complex interplay between tumor cells, endothelium, and stromal cells in angiogenesis. Because little is known about the more precise localization of the interplay between angiogenesis and lymphocytes, this issue should be addressed in future studies.…”
Section: (8) 13 27mentioning
confidence: 99%
“…[1][2][3][4][5] The types of inflammatory cells that infiltrate tumors correlate with patient prognosis. [6][7][8][9] Although tumor cells control the abundance and function of tumor-infiltrating immune cells to create a milieu that supports tumor growth and dissemination, [10][11][12][13][14] the specific genes expressed in tumor cells that create an immunosuppressive microenvironment have not been fully defined.…”
Section: Introductionmentioning
confidence: 99%